SEPARATENESS AND CONNECTEDNESS: A STUDY OF WAR NARRATIVE IN VAN BOOY’S THE ILLUSION OF SEPARATENESS - Sufen Wu (Sanata Dharma University, 2022)
Simon Van Booy, an emerging British novelist, continues to write about war but narrows it down to the separateness and connectedness of war in his novel The Illusion of Separateness. Van Booy takes advantage of a series of narrative strategies to create the illusion of separateness at the surface level, but at the deep level of the novel, he reveals that war makes people closely connected with each other, which can be seen in the interlaced, elliptical character relationship diagram of three generations. Therefore, this study, drawing on narrative theory, endeavors to investigate Van Booy’s war writing in The Illusion of Separateness and explore how the writer uses narrative devices to emphasize the natural elements of war, namely separateness and connectedness. By expounding on these elements and the war narrative in this novel, we can see Van Booy’s unique thinking on war and also have a deeper understanding of war.